Modularized laparoscopic regional en bloc mesogastrium excision (rEME) based on membrane anatomy for distal gastric cancer - Shen, Jian (Surg Endosc, 2018)
BACKGROUND: The purpose of the study was to evaluate the safety and feasibility of a new surgical procedure named modularized laparoscopic regional En bloc mesogastrium excision (rEME) based on the membrane anatomy in distal laparoscopic radical gastrectomy for gastric cancer. METHODS: From January 2014 to June 2017, 92 consecutive cases of patients with stages I–III distal gastric cancer were divided into 2 groups: laparoscopic radical gastrectomy plus standard D(2) lymph node dissection (SD group, n = 44) and modularized rEME (rEME group, n = 48). Evaluations were made in terms of the operative data, pathological results, recovery time of digestive tract functions, complications, and length of stay. RESULTS: 85 patients (SD group, n = 40 and rEME group, n = 45) were finally included for analysis. There were no significant differences in the median total numbers of dissected LNs (31.98 ± 10.48 vs. 34.93 ± 13.12, p = 0.261), LNs in the greater curvature (12.18 ± 6.55 vs. 13.62 ± 8.09, p = 0.444), LNs in the lesser curvature (19.55 ± 7.40 vs. 17.98 ± 8.31, p = 0.365) between the SD and rEME groups. The rEME group showed lower loss of blood volume (107.11 ± 60.13 ml vs. 146.25 ± 85.78 ml, p = 0.019). No significant differences were found in recovery time of digestive tract functions, postoperative complication rates and length of hospital stay between the two groups. CONCLUSION: Laparoscopic radical gastrectomy plus modularized rEME based on the membrane anatomy is a safe and feasible procedure for distal gastric cancer.